2001
DOI: 10.1177/00220345010800061301
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of MMP Inhibitors on Human Salivary MMP Activity and Caries Progression in Rats

Abstract: Previous studies suggest that salivary and pulp-derived host enzymes, matrix metalloproteinases (MMPs), may be involved in dentin caries pathogenesis. To study the inhibition of acid-activated human salivary MMPs by non-antimicrobial chemically modified tetracyclines (CMTs), we used a functional activity assay with 125I-labeled gelatin as a substrate. To address the role of MMPs in the progression of fissure caries in vivo, we administered the MMP inhibitors CMT-3 and zoledronate to young rats per os for 7 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
0
19

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(168 citation statements)
references
References 22 publications
(37 reference statements)
5
144
0
19
Order By: Relevance
“…The acidic environment created by bacterial acids can facilitate the activation of endogenous MMPs. Low pH leads to the cleavage of prodomain and thus facilitates the functional activity of MMPs (Tjäderhane et al 1998;Sulkala et al 2001). However, although activated MMPs are stable in acidic pH, they function best at neutral pH.…”
Section: Dental Caries and Role Of Mmps In Caries Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acidic environment created by bacterial acids can facilitate the activation of endogenous MMPs. Low pH leads to the cleavage of prodomain and thus facilitates the functional activity of MMPs (Tjäderhane et al 1998;Sulkala et al 2001). However, although activated MMPs are stable in acidic pH, they function best at neutral pH.…”
Section: Dental Caries and Role Of Mmps In Caries Progressionmentioning
confidence: 99%
“…CMT-5, a tetracycline analogue with a very low MMP-inhibitory effect compared with CMT-3, had practically no effect of rat molar caries (Tjäderhane et al 1999;Sulkala et al 2001). CMT-3 also eliminates the human salivary gelatinase activity (Sulkala et al 2001), and systemic doxycycline medication has a . MD = mineralized dentin; T = dentinal tubules; A = filled adhesive.…”
Section: Therapeutic Mmp Inhibitors In Caries Progression and Bond Stmentioning
confidence: 99%
“…Inhibitors of endogenous dentin proteases other than CHX, such as the quaternary ammonium surface-acting benzalkonium chloride (BAC) 124,125,126,127 the tetracyclines (TCs) and their antimicrobially inactive analogs (minocycline, for now), 71,84,128,129,130 bisphosphonates (batimastat, galardin, and zoled ron ate), 93,129,131,132 g reen tea poly phenol epigallocatechin-3-gallate (EGCG), 40,133,134 and the chelating agent ethylenediaminetetraacetic acid (EDTA) 135,136,137 are being studied as better alternatives associated with dentin hybrid layer preservation.…”
Section: Enzymatic Inhibitorsmentioning
confidence: 99%
“…As the maintenance of the organic matrix is desirable to decrease the progression of erosive dentin lesions 2 , it seems worth to analyse whether the application of potential MMP inhibitors affects indirectly the progression of erosion by reducing the organic breakdown. Previous studies found that the application of potential MMP-inhibitors reduced the dentin collagen solubilisation 10 and diminished the progression of caries lesions in rats 11 . One potent MMP-inhibitor affecting MMP 2, 8 and 9 is chlorhexidine 12 , which was shown to reduce the degradation of the dentin hybrid layer 13 and the solubilisation of dentinal collagen 10 .…”
Section: Introductionmentioning
confidence: 96%